Partial Least Square Second Order dengan Pendekatan Two Stage untuk Mengukur Tingkat Adopsi Digital UMKM - Sakinah, Awit; Listiani, Lina; Agustina, Nova (Jurusan Matematika FMIPA UNM, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Tasikmalaya have a relatively low rate of technology adoption, particularly in e-commerce. Initial survey results show that 66% of MSMEs supported by the Tasikmalaya Kamar Dagang Industri (KADIN) have not been able to leverage e-commerce adoption. This limitation significantly impacts the growth of MSMEs and their ability to compete in a market increasingly integrated with digital technology. This study aims to analyze the factors influencing the adoption of e-commerce by MSMEs in Tasikmalaya using the Technology Acceptance Model (TAM). The analysis method employs Partial Least Square (PLS) Second Order, as the variables in TAM are multidimensional. The second-order approach selected is the two-stage method, which can minimize residuals of correlated indicators. Data were collected using simple random sampling with a rule-of-thumb sample size of 145 MSMEs. The study results indicate a significant influence of self-efficacy on perceived usefulness and perceived ease of use. There is also a significant influence of perceived ease of use on perceived usefulness. Additionally, perceived usefulness and perceived ease of use significantly and positively influence attitudes toward e-commerce adoption among MSMEs, with a total influence of 87.2%. Furthermore, there is a significant influence of perceived usefulness and attitude towards e-commerce adoption on intention to adopt e-commerce by 91.5%. The intention to use e-commerce significantly affects actual use (adoption) by 91.1%. This indicates that the more positive the perception of usefulness and ease of technology, the higher the intention and actual use of e-commerce technology by MSMEs. To increase e-commerce adoption among Tasikmalaya MSMEs, training on user-friendly e-commerce platforms and intensive mentoring is needed to enhance the self-efficacy of MSME actors in utilizing technology.